2009
DOI: 10.1021/ie901005a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Emulsification Devices for the Production of Miniemulsions

Abstract: Droplets generated using ultrasonication, the rotor-stator, and static mixers have been investigated in terms of power and energy consumption, droplet distributions, and shear rates. It was observed that with energy costs being of similar orders of magnitude, the static mixers imposed less shear on the system making them the optimal choice for miniemulsification. Similarly, the absolute widths of the distributions for droplets generated with the sonicator and rotor-stator were larger than those generated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…A transducer contains piezoelectric crystals, which, upon receiving the electrical signal, start to oscillate, causing the horn or probe to longitudinally expand and contract. Emulsification occurs because these pressure waves lead to the creation of voids within the continuous phase, which implode violently when they have reached a critical size [67]. This is known as transient cavitation.…”
Section: Ultrasonicationmentioning
confidence: 99%
“…A transducer contains piezoelectric crystals, which, upon receiving the electrical signal, start to oscillate, causing the horn or probe to longitudinally expand and contract. Emulsification occurs because these pressure waves lead to the creation of voids within the continuous phase, which implode violently when they have reached a critical size [67]. This is known as transient cavitation.…”
Section: Ultrasonicationmentioning
confidence: 99%
“…High-pressure homogenisers (HPH) have also been found to be effective for laboratory and industrial scale experiments. [2] Similar to US, HPH devices are energy intensive and sometimes require a pre-homogenisation step to reduce the number of cycles (a cycle is defined by the time needed to pass the entire volume once through the shearing zone). More recently it has been shown that alternative devices such as rotor-stators and static mixers impose less shear [3] and are capable of generating large volumes of polymerisable miniemulsions making them more suitable for scale-up.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used are the high frequency ultrasonic devices, the high pressure homogeneizers (HPH), and the microfluidizers [30,39]. The use of ultrasounds for emulsification is increasingly studied for its lower energy consumption, its use of fewer amounts of surfactants, and the obtainment of smaller sizes for more homogeneous products than classical mechanical processes [29,39,40]. The use of ultrasounds for emulsification is increasingly studied for its lower energy consumption, its use of fewer amounts of surfactants, and the obtainment of smaller sizes for more homogeneous products than classical mechanical processes [29,39,40].…”
Section: Fabrication Proceduresmentioning
confidence: 99%